2018
DOI: 10.1152/ajpcell.00135.2018
|View full text |Cite
|
Sign up to set email alerts
|

Expansion capacity of human muscle progenitor cells differs by age, sex, and metabolic fuel preference

Abstract: Activation of satellite cells and expansion of the muscle progenitor cell (MPC) population is essential to generate a sufficient number of cells to repair damaged skeletal muscle. Proliferating MPCs have high energetic and biosynthetic material requirements, and the ability to utilize oxidative phosphorylation (OXPHOS) and/or glycolysis may affect expansion capacity of MPCs. In the present study, we investigated whether donor age and sex impact human MPC (hMPCs) expansion capacity and metabolic fuel preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The last decade has been an exciting period for the study of the biology of skeletal muscle stem cells and tissue regeneration and the development of novel human in vitro cell models can contribute to the identification of new mechanisms that control myogenesis [14][15][16][17][18][19][20]. These human cell cultures appear more suitable for predictive screening strategies when compared to rodent cell lines, such as C2C12 or rat L6 myoblasts [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has been an exciting period for the study of the biology of skeletal muscle stem cells and tissue regeneration and the development of novel human in vitro cell models can contribute to the identification of new mechanisms that control myogenesis [14][15][16][17][18][19][20]. These human cell cultures appear more suitable for predictive screening strategies when compared to rodent cell lines, such as C2C12 or rat L6 myoblasts [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that USP2 contributes to the generation of sufficient ATP by OXPHOS in myoblasts. On the other hand, Usp2 KO cells exhibited impairments in proliferation and differentiation, both of which require an adequate glucose‐derived energy supply by the mitochondria (Elkalaf et al, ; Riddle et al, ). Collectively, these results suggest that USP2 might control proliferation and differentiation in myoblasts through sustained activation of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Although myofibers preferentially obtain ATP by OXPHOS, satellite cells and myoblasts may acquire ATP predominantly by glycolysis (Leary et al, 1998;Sin et al, 2016;Wagatsuma and Sakuma, 2013). On the other hand, a previous study demonstrated that the differentiation and proliferation of myoblasts is highly dependent on both OXPHOS and glycolysis (Riddle et al, 2018). Therefore, activated myoblasts seem to utilize both OXPHOS and glycolysis for ATP supply.…”
Section: Introductionmentioning
confidence: 98%
“…Young (21–40 years) and old adults (65–80 years) were recruited from the Ithaca, New York and Boone, North Carolina areas (participant characteristics in Supplementary Table S1) in a manner previously published (Riddle et al, 2018a,b). The Cornell University and Appalachian State University Institutional Review Boards approved the protocols.…”
Section: Methodsmentioning
confidence: 99%